Understanding the fate of DNA nanostructures inside the cell. Issue 29 (2nd April 2020) - Green, Christopher M.; Mathur, Divita; Medintz, Igor L.
Abstract : DNA nanostructures are highly tunable and responsive materials for diagnostic and healthcare-related applications, but their intracellular fate remains largely unknown. Abstract : Structural DNA nanotechnology is poised to transform targeted therapeutic and theranostic delivery agents. Some of the most promising biomedical applications of DNA nanostructures include carriers for biosensing, imaging, and drug delivery. Additionally, the unique ability to precisely position inorganic and organic molecules on DNA-based substrates enables the spatially optimized high density interfacing of ligands with cell membrane receptors. To realize clinically viable biomedical products made from DNA nanostructures, it is necessary to fully understand the behavior of these systems inside and outside the cellular environment. To that end, cohesive and conclusive information on the physiological fate of DNA nanostructures at various time points – from the cell culture to the cell cytosol – is still lacking. In this highlight, we bring to attention efforts to understand DNA nanostructure behavior in vitro as well as some widespread disparities among studies on the subject. We also call for a discussion on the implementation of common standards and controls to address these disparities and consequently unify the scientific community's endeavours to build foundational knowledge on DNA nanostructure–cellular interaction.